Galactan exopolysaccharide based flavour emulsions and their application in improving the texture and sensorial properties of muffin. (October 2020) - Kavitake, Digambar; Kalahasti, Krishna Kalyan; Devi, Palanisamy Bruntha; Ravi, Ramasamy; Shetty, Prathapkumar Halady
Abstract: In this study, food grade flavour emulsions of vanilla and cardamom were prepared with galactan exopolysaccharide (EPS) isolated from Weissella confusa KR78067. Galactan flavoured emulsions (GFE) were lyophilized and studied for their physical properties such as colour analysis, bulk density and tapped density followed by application in muffin. Fourier transform infrared spectroscopy of GFE vanilla and GFE cardamom has revealed the presence of vanilla and cardamom flavouring compounds in the powdered emulsions. Scanning electron microscopy of emulsions exposed smooth, spherical appearance with evenly dispersed particles. Particle size analysis of GFE vanilla and GFE cardamom disclosed similar size molecules. Colour evaluation showed increment of brownish appearance whereas flow properties like bulk density and tapped density revealed the particle arrangement and compactness of GFE vanilla and GFE cardamom. Further GFE vanilla has been incorporated in muffin to demonstrate the practical application of galactan based flavour emulsions in food products. Colour (crust and crumb) and texture analysis revealed the high chroma, springiness and cohesiveness for the GFE vanilla muffins. Sensory properties showed higher acceptability for the GFE vanilla muffins compare to control, hence promoting this EPS as a suitable bioemulsifier for flavours and bioactive compounds in food and pharmaceutical applications. Graphical abstract: Image 1